S6 kinase 1 at the central node of cell size and ageing - Fumagalli, Stefano; Pende, Mario (Frontiers in Cell and Developmental Biology, 2022)
Genetic evidence in living organisms from yeast to plants and animals, including humans, unquestionably identifies the Target Of Rapamycin kinase (TOR or mTOR for mammalian/ mechanistic) signal transduction pathway as a master regulator of growth through the control of cell size and cell number. Among the mTOR targets, the activation of p70 S6 kinase 1 (S6K1) is exquisitely sensitive to nutrient availability and rapamycin inhibition. Of note, in vivo analysis of mutant flies and mice reveals that S6K1 predominantly regulates cell size versus cell proliferation. Here we review the putative mechanisms of S6K1 action on cell size by considering the main functional categories of S6K1 targets: substrates involved in nucleic acid and protein synthesis, fat mass accumulation, retrograde control of insulin action, senescence program and cytoskeleton organization. We discuss how S6K1 may be involved in the observed interconnection between cell size, regenerative and ageing responses.